Comparative analysis of correlation between investments in science, technology & innovation and socioeconomic development in the face of global megatends - Seibert, Caroline Heidrich; Neto, João Pinheiro de Barros (Seven Editora, 2023)
In today's world, innovation guides a country's ability to adapt and conquer new markets, being investments in Science, Technology and Innovation (CT&I) one of the essential factors to keep up with global megatends. This work aimed to know the correlations between socioeconomic development indicators of 14 countries, including Brazil, and CT&I performance indicators. The results demonstrated high correlations between gross investments in CT&I and GDP, as well as the position in scientific production (R2 = 0.85 in both analyzes). The correlation of investments in CT&I with the ranking of competitiveness was low; However, the innovation ranking showed median correlation (R2 = 0.61) when related to the CT&I invested GDP percentages. The correlations between the innovation and competitiveness rankings with the HDI were also median (R2 = 0.61 and R2 = 0.56, respectively). CT&I indicators did not correlate with GDP growth rates and unemployment rates. Thus, this study infers that investing a higher percentage of GDP in CT&I can promote greater ability to innovate and human development in a country, and may be a political-economic strategy to be adopted.DOI: https://doi.org/10.56238/devopinterscie-008